Information asymmetry and search intensity - Atabek Atayev (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2023)
In markets where sellers' marginal costs of production have a common component, they have informational advantage over buyers regarding those costs. This information asymmetry between sellers and buyers is especially relevant in markets where buyers have to uncover prices through costly search. We propose a theoretical model of simultaneous search that accounts for such information asymmetry. Our main finding is that informing buyers about marginal costs may harm them by deterring search and, hence, softening competition. This result has important implications on policy regulations and voluntary information sharing.
Keywords: D43; D83; L13; 330; Information Asymmetry; Consumer Search; Price Competition